2007
DOI: 10.1016/j.neuroimage.2007.04.061
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral control of the bladder in normal and urge-incontinent women

Abstract: Aim: To identify age-related changes in the normal brain/bladder control system, and differences between urge incontinence in younger and older women, as shown by brain responses to bladder filling; and to use age, bladder volume, urge incontinence and detrusor overactivity (DO) as probes to reveal control-system function. Functional MRI was used to examine regional brain responses to bladder infusion in 21 females (26 -85 years): 11 "cases" with urge incontinence and DO (proven previously) and 10 normal "cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
175
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(191 citation statements)
references
References 34 publications
13
175
2
1
Order By: Relevance
“…Such activation appears to be significantly stronger in incontinent subjects during reported urgency albeit decreasing with advanced age (9,12).…”
Section: R I G H T a N T E R I O R I N S U L Amentioning
confidence: 84%
See 2 more Smart Citations
“…Such activation appears to be significantly stronger in incontinent subjects during reported urgency albeit decreasing with advanced age (9,12).…”
Section: R I G H T a N T E R I O R I N S U L Amentioning
confidence: 84%
“…In addition, fMRI studies have shown that the PMC responds to bladder filling during the storage phase as well (both in normal subjects and in urge incontinent subjects prior to onset of detrusor overactivity, DO) (8)(9)(10). Thus imaging studies indicate that PMC responses during the storage phase represent inhibition of the PMC and the voiding reflex.…”
Section: P O N T I N E M I C T U R I T I O N C E N T E R ( P M C )mentioning
confidence: 98%
See 1 more Smart Citation
“…11 Yang et al 12 compared children with ADHD to children with ADHD and enuresis, and observed the latter had shorter response times in neuropsychological tests devised to assess attentional performance, revealing they had less inhibitory control. Understanding this pathophysiological correlation and the importance of treating psychiatric comorbidities are key steps lower urinary tract dysfunction: 56% of the children postponing voiding had clinical-range scores in the CBCL versus 24% of the children with urinary incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…These afferent signals activate sympathetic pathways in the hypogastric and pudendal nerves, which lead to contraction of the smooth and striated sphincters, and at the same time inhibit detrusor contraction. In addition, high cortical centers are activated, (Griffiths et al, 2007), and stimulate the storage center in the pons. (Fowler et al, 2008) When further bladder filling leads to increased afferent signaling from the bladder, spinobulbospinal reflex pathways are carried via the pelvic nerve and spinal cord to the pontine micturition center, which activates parasympathetic pathways that cause bladder contraction and inhibit sympathetic and pudendal contraction of the sphincter (Fowler et al, 2008) For coordinated micturition to occur, parasympathetic stimulation of the detrusor occurs via cholinergic muscarinic receptors.…”
Section: Normal Micturitionmentioning
confidence: 99%